Dinamika Transformasi Tasawuf Era Modern: Neo-Sufisme dan Gerakan Islam Transnasional - Ahmad Fahrur Rozi,; Nurwahidin,; Mulawarman Hannase, (Tasamuh: Jurnal Studi Islam, 2024)
This article examines the dynamics transformation of Sufism in the modern era. Sufism in the modern era appears running into transformation both in terms of its concept and movement. From the aspect of the concept of Sufism, modern Sufism is running into a transformation, namely neo-Sufism. Likewise, in the network aspect of the Sufism movement in the modern era, Sufism moves dynamically, from a local movement to becoming a network of transnational Islamic movements. This research is qualitative research using transnationalism theory as an analytical tool and historical studies as an approach. In this research, at least two findings were found. First, the presence of neo-Sufism is a form of transformation of classical Sufism teachings. The concept of neo-Sufism tends to be balanced (tawazun) between exoteric and esoteric aspects and can be a spiritual alternative for urban Muslim communities. Second, modern Sufism can be categorized as a representation of a transnational Islamic movement, as a non-governmental movement structured across countries in terms of thought, spiritual and political movements. The main route behind the transnational Islamic movement of Sufism is through da'wah, trade and immigrants. Keywords: Sufism, Neo-Sufism, Transnationalism, Transformative